PERANCANGAN LKPD MATEMATIKA BERBASIS ELICITING ACTIVITIES UNTUK MENINGKATKAN PENGUASAAN KONSEP SEGITIGA PADA SISWA KELAS VII - Imayan Nur Latifah (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2025)
This study aims to design and evaluate the quality of Mathematics Student Worksheets (LKPD) based on Eliciting Activities (MEAs) for seventh-grade students at MTs Miftahul Huda Lehan. The main issue addressed in this research is how to develop LKPD that meet the criteria of validity, practicality, and effectiveness as instructional materials for the topic of triangles. The study employed a Research and Development (R&D) method by adapting a development model consisting of the stages of design, expert validation, limited trials, and evaluation. The resulting product is an LKPD developed based on MEAs principles to encourage students’ ability to independently construct mathematical concepts. The test subjects in this study were seventh-grade students at MTs Miftahul Huda Lehan. Data were collected through validation sheets completed by material and media experts, as well as questionnaires administered to teachers and students. The expert validation results indicated that the LKPD met the validity criteria, with average scores categorized as “very good.” Teachers' responses to the LKPD yielded an average score of 87.5%, categorized as “very interesting,” indicating that the LKPD is practical for classroom use. Meanwhile, students’ responses yielded an average score of 86.8%, also categorized as “very interesting.” These findings demonstrate that the MEAs-based LKPD developed in this study is not only valid and practical but also effective in enhancing students’ engagement and conceptual understanding. Therefore, the MEAs-based mathematics LKPD produced in this study is suitable for use as instructional material for the topic of triangles and has the potential to improve the quality of the learning process.